Histological Typing of Endocrine Tumours - Solcia, Enrico; Klöppel, Günter; Sobin, Leslie H. (WHO. World Health Organization. International Histological Classification of Tumours, 2000)
The second edition of this book updates the WHO Classification of Endocrine Tumours proposed in 1980 and incorporates many new tumour entities and pertinent concepts that have developed since that time. It is the result of a collaborative effort of 9 pathologists from different countries, in addition to informal contributions and discussions by many other colleagues. Efforts have been especially made to integrate into the fundamental backbone of the histologic classification a number of prognostic and functional parameters now essential for appropriate diagnosis and clinico-pathologic evaluation of endocrine tumours